2007
DOI: 10.1111/j.1365-2796.2007.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, its preeminent clusters, incident coronary heart disease and all‐cause mortality – results of prospective analysis for the Atherosclerosis Risk in Communities study

Abstract: Objective. To investigate the prospective association between Metabolic Syndrome (MetS) and coronary heart disease (CHD) and all-cause mortality.Subjects and Design. A bi-racial cohort of 14 699 middle-aged Americans from the Atherosclerosis Risk in Communities study were followed for the development of new CHD and death over a period of 9 years. MetS, using the original ATP-III criteria, was defined as having at least three of the following components: elevated blood pressure (BP), elevated plasma glucose, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 57 publications
2
71
2
4
Order By: Relevance
“…29 Published studies performed by our group have looked at the association of MetS with the risk of incident coronary heart diseases and all-cause mortality in the ARIC population. 30 For the purpose of this particular study, we used similar approaches like those shown by Hong et al 30 to look at MetS and the risk of incident stroke in the ARIC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…29 Published studies performed by our group have looked at the association of MetS with the risk of incident coronary heart diseases and all-cause mortality in the ARIC population. 30 For the purpose of this particular study, we used similar approaches like those shown by Hong et al 30 to look at MetS and the risk of incident stroke in the ARIC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Among the more prominent data sets are those of the Framingham Study, including the Framingham Offspring Study, in the United States, and the General Practice Research Database in the United Kingdom, the largest non-US database of ''anonymized'' primary care medical records. 14,15 Turning to the effects of body mass index (BMI) and obesity, Bays and colleagues 16 explored the relationships between BMI and prevalence of diabetes, hypertension, and dyslipidemia, examined BMI distributions among patients with these conditions, and compared results from 2 national surveys: (1) the screening questionnaire-based 2004 Study to Help Improve Early evaluation and management of risk factors Leading to Diabetes (SHIELD), and (2) the interview, clinical, and laboratory data of the 1999-2002 National Health and Nutrition Examination Surveys (NHANES).…”
mentioning
confidence: 99%
“…Additionally, longitudinal studies have demonstrated variations in the risk of mortality according to the different combination patterns of metabolic syndrome components. 29,30 In our study, we observed that the most frequent We believe that our findings have a social impact because the study population was still undergoing the process of epidemiological transition, i.e. high rates of morbidity and mortality due to infectious and parasitic diseases 35 were observed to coexist with increased occurrence of non-communicable illnesses.…”
Section: Discussionmentioning
confidence: 57%